Experimental study of tubal uterine contractility in women - Stabile, Americo (2015)
As a result of our experimental study and the conclusions arrived, it left open, as sediment and helpful indisputable value of future, a wide field for the study of the pathophysiology of uterine muscle in gynecology and research subsidiary.